Worshiping the goddess Jyeshtha Gauri - Mumbai Archive Project Team (Jio Institute, 2024)
Unlike Ganesh Chaturthi, which is publicly celebrated all over Mumbai on a grand scale, Gauri Puja is a modest household event, performed by families inside their homes. In coastal Maharashtra, Gauri is worshipped as a singular Goddess known as Jyeshtha Gauri (jyestha meaning the elder one or the senior). The Goddess is installed on a high platform.